2020
DOI: 10.1080/10584609.2020.1840462
|View full text |Cite
|
Sign up to set email alerts
|

Believing and Sharing Information by Fake Sources: An Experiment

Abstract: The increasing spread of false stories ("fake news") represents one of the great challenges societies face in the 21st century. A little-understood aspect of this phenomenon and of the processing of online news in general is how sources influence whether people believe and share what they read. In contrast to the predigital era, the Internet makes it easy for anyone to imitate well-known and credible sources in name and appearance. In a preregistered survey experiment, we first investigate the effect of this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 89 publications
1
13
0
3
Order By: Relevance
“…One element behind the similar effects of familiar and unfamiliar news outlets is the charitable assessments unfamiliar media sources received. People regarded unknown media as somewhat trustworthy and presumed they were moderate rather than viewing them as untrustworthy and ideologically incongruent, a finding consistent with some other work considering unknown and fictional news sources (see Bauer and von Hohenberg 2020;Greer 2003;Sterrett et al 2019). 13 This differs from Pennycook and Rand (2019), who find unfamiliar fake and hyperpartisan outlets are largely mistrusted.…”
Section: Charitable Views Of Unfamiliar Mediasupporting
confidence: 78%
See 1 more Smart Citation
“…One element behind the similar effects of familiar and unfamiliar news outlets is the charitable assessments unfamiliar media sources received. People regarded unknown media as somewhat trustworthy and presumed they were moderate rather than viewing them as untrustworthy and ideologically incongruent, a finding consistent with some other work considering unknown and fictional news sources (see Bauer and von Hohenberg 2020;Greer 2003;Sterrett et al 2019). 13 This differs from Pennycook and Rand (2019), who find unfamiliar fake and hyperpartisan outlets are largely mistrusted.…”
Section: Charitable Views Of Unfamiliar Mediasupporting
confidence: 78%
“…Closest to our focus, several studies ask people to assess the trustworthiness of unfamiliar or fictional news outlets. Although coverage from these sources is typically evaluated as less credible than coverage from real sources (but see Dias, Pennycook, and Rand 2020), news from fictional outlets with innocuous names (e.g., "DailyNewsReview.com") is still typically rated as relatively trustworthy (Bauer and von Hohenberg 2020;Greer 2003;Sterrett et al 2019).…”
Section: Responding To News From Unfamiliar Mediamentioning
confidence: 99%
“…People are more likely to share accurate than fake new, but "interestingness" can compensate some lack of accuracy . Furthermore, sources matter: an experiment found that users are more likely to believe fake news if they come from sources that previously supplied them with information congruent with their political beliefs (Bauer and von Hohenberg, 2020).…”
Section: Fake Newsmentioning
confidence: 99%
“…political communication, health communication, and crisis communication) have studied it, examining a wide range of factors. Some have examined the effects of information attributes on sharing behaviors, such as message source (Bauer and Von Hohenberg, 2021), sentiment (Kumar et al, 2021), and labels (Lynn et al, 2017). Some studies examined the differences at the individual level, such as ideology, cognitive reflection, conscientiousness, self-disclosure level , and personality (Apuke and Omar, 2021; He et al, 2019; Hopp et al, 2020; Lee and Oh, 2017; Pennycook et al, 2020).…”
mentioning
confidence: 99%